Perhitungan Kebutuhan Air Irigasi untuk Perluasan Daerah Irigasi (Studi Kasus: Daerah Irigasi Cisadeng II, Desa Leuwisadeng, Kecamatan Leuwisadeng, Kabupaten Bogor) - Rahayu, Uga Sri; Hariati, Feril; Alimuddin, Alimuddin; Nandiasa, Jantiara Eka (Universitas Ibn Khaldun, 2023)
The need for irrigation water as a whole need to be known in the planning and management of irrigation systems. Given that the Cisadeng II Irrigation Area (DI) located in Leuwisadeng District, Bogor Regency, experienced an expansion of the paddy field area from 32 ha to 42 ha, it is necessary to carry out an analysis of the demand for irrigation water discharge on various cropping patterns. This study used two methods, namely manual calculation (KP-01 concept) and calculation using the CROPWAT application version 8.0. This study aims to compare the results of the two calculations. From the results of the study, the amount of irrigation water needed for rice cropping pattern with the beginning of land preparation in November, with manual calculations (KP-01 concept) using the modified Penman method is 8.12 - 19.00 m3/sec. Meanwhile, according to CROPWAT Version 8.0 calculations, it is 8.03 - 18.39 m3/sec. Thus, it can be concluded that the calculations with the two methods do not give too different values. In addition, from the results of calculating the reliable debit, the use of the CROPWAT Version 8.0 method provides a more accurate value. Keywords: Irrigation, water demand, manual calculation (KP-01), CROPWAT Version 8.0